Nutritional Analysis of Mature Unripen and Ripen Edible Fruits of Aegle tamilnadensis Abdul Kader (Rutaceae) - M. Chellakumar; S. Abdul Kader (Journal of Pharmacy and Nutrition Sciences, 2019)
Nutritive analysis of mature unripe and ripe fruits of Aegle tamilnadensis which is a close relative of A. marmelos (L) Correa was carried out at Presidency College, Chennai during 2016. Mature unripen fruits were plucked from the tree while ripen fruits were gathered from the ground after their natural fall during the month of December 2016 from the campus of Govt. Siddha Medical College, Arumbakkam, Chennai, Tamil Nadu, India. Seeds were removed; fresh fruit pulp was collected and weighed. Such pulp was used for the extraction of nutrients using methanol in Soxtron apparatus (Socs Plus - SCS 06 E). The moisture content was estimated by hot air oven method and expressed on dry weight basis [10]. The methanol fruit pulp extracts were used with standard methods for the estimation of protein, carbohydrate (sugar), energy, fat, vitamins, and minerals such as calcium, sodium and iron. The results showed that the mature unripe fruit contain high protein, sodium and calcium contents while cholesterol and fat contents were lower than those present in the ripe fruits. On the contrary in ripe fruit, vitamin C and iron contents were high. Therefore, both mature unripe and ripe fruits of Aegle tamilnadensis Abdul Kader can be used as a potential natural nutraceutical.